1997
DOI: 10.1093/emboj/16.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic potential of TAR RNA binding protein TRBP and its regulatory interaction with RNA-dependent protein kinase PKR

Abstract: TAR RNA binding protein (TRBP) belongs to an RNA binding protein family that includes the double‐stranded RNA‐activated protein kinase (PKR), Drosophila Staufen and Xenopus xlrbpa. One member of this family, PKR, is a serine/threonine kinase which has anti‐viral and anti‐proliferative effects. In this study we show that TRBP is a cellular down‐regulator of PKR function. Assaying expression from an infectious HIV‐1 molecular clone, we found that PKR inhibited viral protein synthesis and that over‐expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
211
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(219 citation statements)
references
References 71 publications
(140 reference statements)
8
211
0
Order By: Relevance
“…This observation was ascribed to a trans-dominant inhibitory effect of the mutant enzyme on the endogenous wild-type PKR and implicated PKR as a tumor suppressor gene. In addition, overexpression of a nonphosphorylatable Ser51Ala mutant eIF-2␣ (Donze et al 1995), as well as the PKR inhibitors p58 IPK and HIV TAR RNA-binding protein (TRBP) also displayed transforming activity (Barber et al 1994;Benkirane et al 1997). It was also demonstrated that overexpression of wild-type PKR can inhibit protein synthesis and cell growth in yeast and in mammalian cells (Chong et al 1992;Thomis and Samuel 1992).…”
Section: Stress-induced Eif-2␣ Phosphorylation Activates Apoptosismentioning
confidence: 99%
“…This observation was ascribed to a trans-dominant inhibitory effect of the mutant enzyme on the endogenous wild-type PKR and implicated PKR as a tumor suppressor gene. In addition, overexpression of a nonphosphorylatable Ser51Ala mutant eIF-2␣ (Donze et al 1995), as well as the PKR inhibitors p58 IPK and HIV TAR RNA-binding protein (TRBP) also displayed transforming activity (Barber et al 1994;Benkirane et al 1997). It was also demonstrated that overexpression of wild-type PKR can inhibit protein synthesis and cell growth in yeast and in mammalian cells (Chong et al 1992;Thomis and Samuel 1992).…”
Section: Stress-induced Eif-2␣ Phosphorylation Activates Apoptosismentioning
confidence: 99%
“…In support of antiproliferative e ects of PKR, overexpression of wild type protein results in slow growth in yeast (Chong et al, 1992) and causes apoptosis in mammalian cells (Balachandran et al, 1998;Der et al, 1997;Donze et al, 1999;Lee et al, 1997;Yeung and Lau, 1998). A mutant form of eIF2 that cannot be phosphorylated by PKR was also observed to transform cells (Donze et al, 1995), as does TRBP, a cellular inhibitor of PKR (Benkirane et al, 1997). Expression of another cellular inhibitor of PKR, p58, also transforms cells (Barber et al, 1994).…”
mentioning
confidence: 89%
“…2B). It is currently implicated in counteracting PKR activity, which results in the proliferative and oncogenic effects in cells (26). Therefore, the direct interaction between merlin tumor suppressor and oncogenic TRBP might have biological significance in regulating cell proliferation.…”
Section: Identification Of Trbp As a Merlin-binding Protein-tomentioning
confidence: 99%
“…TRBP also directly binds the double-stranded RNAdependent protein kinase (PKR) that has anti-viral and antiproliferative effects. TRBP inhibits the ability of PKR to phosphorylate eukaryotic translation initiation factor 2, leading to its inactivation (25,26). In relation to the inhibition of PKR activity, TRBP was recently demonstrated to play a growth promoting role and has an oncogenic potential (26).…”
mentioning
confidence: 99%